Comparison of Co-loading and Preloading for Lower Segment Caesarean Section Under Spinal Anaesthesia - Mehak, Samra; Mehmood, Hamid; Ali, Mumtaz; Kirshan, Bhagwanti (Journal of Neonatal Surgery, 2025)
Background: Spinal anaesthesia is a preferred technique for lower segment caesarean section (LSCS) due to its rapid onset and reliability. However, it is frequently associated with maternal hypotension, which can adversely affect both mother and fetus. Objectives: To compare the efficacy of crystalloid co-loading versus preloading in preventing maternal hypotension in patients undergoing caesarean section under spinal anaesthesia. Study Design & Setting: This study conducted at the Department of Anesthesiology, Dow University of Health Sciences Hospital, Karachi. Methodology: A total of 100 ASA II parturients aged 20–40 years, undergoing elective LSCS, were randomly assigned into two equal groups (preload and co-load). Group P received 15 ml/kg of crystalloids 10–15 minutes before spinal anaesthesia, while Group C received the same volume immediately after spinal injection. Hemodynamic parameters were monitored intraoperatively. Hypotension, nausea, vomiting, bradycardia, and vasopressor use were recorded. Results: Hypotension occurred in 52% of the preload group compared to 30% of the co-load group (p = 0.03). The need for phenylephrine was significantly higher in the preload group (50% vs. 28%, p = 0.02). Other adverse effects were more frequent in the preload group but not statistically significant. Conclusion: Co-loading with crystalloids was more effective than preloading in reducing the incidence of maternal hypotension and vasopressor requirement during spinal anaesthesia for LSCS .